Reflective and structural characteristics of natural pearl - Muhammad Sufi Roslan; Ahmad Faiz Mat Zin; Rozainita Rosley; Fazreen Batrshia Abdullah; Nur Shazreen Amran; Nur Jannatul Aqilah Rosslan; Muhammad Hasnain Jameel; Syed Zuhaib Haider (Science, Technology, and Communication Journal, 2021)
In this study, we analyzed the reflective and structural nature of natural freshwater pearls that originated from Sabah, Malaysia. Seven color pearls from brightest to darkest ones were examined and analyzed by UV-Vis spectroscopic and electron microscopic techniques. Results showed that the UV-Vis spectrum of black shows that reflection occurs at 530 – 540 nm, 600 – 610 nm, 660 nm, and 690 nm which are reflective of green, yellow, and red. However, it mainly differs from other color spectrums as it shows great absorption at wavelengths 270 – 300 nm. Meanwhile, white pearl reflects most of the visible color at wavelength 400 nm, 450 – 470 nm, 550 nm, 600 – 630 nm, and 665 nm which represent all colors possessed by the visible spectrum. FESEM studies show the formation of tablet structures in smooth layers transition between vaterite and aragonite in black pearl. The structural arrangement of its layers is closer and there are many big circular spots on the copper pearl. Besides, the pearl’s surface looks a bit rough. The layer of aragonite platelets in hexagonal shape gives the pearl's prismatic layer in pinkish pearl. Meanwhile, the arrangement of vaterite layers looks smooth and the layers of the stack are arranged in parallel in white pearl. The different morphology of pearl reflects the different colors as well.